EFEKTIVITAS PERMENKOMINFO NO. 19 TAHUN 2014 TENTANG PENANGANAN SITUS INTERNET BERMUATAN NEGATIF TERHADAP PENYALAHGUNAAN APLIKASI VIRTUAL PRIVATE NETWORK - Farid Priyo Handoko; I Made Hendra Wijaya (Jurnal Hukum Mahasiswa, 2023)
The intellectual development of mankind has brought about great changes that have helped human civilization become more advanced. Along with the advancement of the world of information and communication technology in the digital 4.0 era, Indonesia, as the country with the largest internet users, has also been named the country with the largest VPN downloader in the world. The purpose of this study is to determine the effectiveness of blocking negatively charged internet sites and the effectiveness of preventive efforts in overcoming VPN abuse to open government-blocked sites at the Denpasar City Informatics and Statistics Communication Office. Based on the results of research in the field, it can be stated that Permenkominfo No. 19 of 2014 concerning handling negatively charged Internet sites implemented in Denpasar City is still not effective enough to be implemented.